The Readiness of Self-Manage Oil Palm Farmers at Sekadau District in ISPO Implementation - Eka Jaya Soebirin; Maswadi; Anita Suharyani (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2021)
Based on data from the Directorate General of Plantations in 2018, the tendency of expanding the acreage of self-contained oil palm plantations is continuing. It is feared that the continued expansion of land by both companies and smallholder plantations could cause natural damage and gas emissions that lead to the loss of biodiversity. This has led to a lot of criticism from various parties stating that the palm oil industry is responsible for all the risks that occur. To overcome this, the government implements a governance system (certification) for the entire palm oil industry. Indonesian Sustainable Palm Oil (ISPO) is a certification system issued by Indonesian government to reduce the negative impacts of land expansion and to achieve sustainable palm oil. In its implementation in the field, the implementation of ISPO encounters several obstacles, particularly independent plantations such as difficult and complex legality issues, lack of knowledge that causes a lot of land clearing by burning and continuous land expansion. This research needs to be conducted to see the readiness of independent oil palm smallholders in implementing ISPO with descriptive methods and gap analysis. This research was conducted in Engkersik Village, Sekadau Hilir District, Sekadau Regency, the method of determining the sample was using slovin, amounting to 31 farmers. ISPO consist of 4 principles, criteria and indicators are used as variables in this study. The analysis results of all the principle show that farmers are ready with a readiness percentage of 60.9%, where each principle’s percentage of The Legality of Self-Manage Plantation is 75%, The Organization of Farmers and Management of Self-Manage Plantation is 62%, Environmental Management and Monitoring is 43%, and Continuious Business Improvement is 58%, although there are still gaps in its application. For this reason, it is necessary to carry out more effective socialization and training to farmers to minimize the gap.